Chitosan–Zinc Doped Calcium Silicate Containing Scaffolds for Bone Regeneration - Varsha Mugundhan; Palati Sinduja; Saravanan Sekaran; Tanmay Mandal; Srishti Sharma; Digpal Rana (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The critical-sized bone defect is larger for an organism to heal on its own, and hence, autografting is performed in these cases (e.g., pubic bone), but the amount of tissue regenerated is less; hence, an alternative treatment performed is bone tissue engineering where a temporary constrict is kept, and hence, bone forms and the constrict degrades on its own. Materials and Methods: Fabrication of calcium silicate scaffold is performed, and this obtained solution is lyophilized. This zinc is added to enhance its properties as it is a divalent cation that promotes osteoblastic activity. About 1% chitosan and 0.5% zinc calcium silicate are dissolved in acetic acid, poured into a mold froze at − 20°C, and then lyophilized. Spongy scaffold is, therefore, formed, and its properties are analyzed. Results: SEM analysis, porosity, and swelling ratio were taken to analyze the physio-chemical properties of the scaffold. The swelling ratio when compared shows an increase in zinc-doped scaffold and hence will help in dislodgement of the constriction easily as it helps in easy movement of the nutrients and enhances the tissue formation. Conclusion: The research on deciphering the role of copper-zinc alloy nanoparticles on osteoblast viability and proliferation has provided valuable insights into their potential effects on bone health and regeneration.